Influence of inclusion of pigeon pea (Cajanus cajan) leafmeal on growth, physio‐metabolic and immune parameters, and expression of IGF‐1, IGF‐1R and IGFBP‐1 genes in Labeo rohita (Hamilton, 1822) fingerlings. (19th December 2020) - Rani, Susmita; Sahoo, Sujata; Srivastava, Prem Prakash; Kumar, Munish; Gupta, Subodh; Munilkumar, Sukham; Gupta, Gyandeep; Krishna, Gopal
Abstract: A feeding trial was conducted with inclusion levels of Cajanus cajan leafmeal (CCLM) in the diet of Labeo rohita to study the growth, haematological indices, digestive enzyme, physio‐metabolic changes and molecular expression of insulin‐like growth factor‐1 (IGF‐1), insulin‐like growth factor‐binding protein‐1 (IGFBP‐1), insulin‐like growth factor‐1 receptor (IGF‐1R) genes. Four practical diets with CCLM, control, T20 (20%), T30 (30%) and T40 (40%) were prepared. Weight gain%, SGR, FER and PER were significantly ( p < 0.05) higher when 30% de‐oiled rice bran (DORB) was replaced by CCLM whereas the treatment group 40% registered with lower FCR value. The protease and amylase activities were higher in the T30 group. T20 showed significantly higher ( p < 0.05) hepatic and muscular lactate dehydrogenase and serum glucose was also higher, whereas, WBC content was found significantly ( p < 0.05) higher in control. The hepatic IGF‐1 gene expression was significantly higher ( p < 0.05) in T40 followed by the T30 group but the weight gain was not significantly ( p > 0.05) higher in T30 from the T40 group. Results reveal that the response of IGF‐1, IGF‐1R and IGFBP‐1 genes was complementary to the biological growth parameters and hence were used as an indicator to evaluating growth. The study also demonstrates that CCLM can replace 100% DORB in the diet of L. rohita without any antinutritional or adverse growth effects.